Cal Poly Choirs "A Christmas Celebration" Concert - Music Department::::::author::: (2008)
Concert flyer for the Cal Poly Choirs "A Christmas Celebration" concert. Red floral background with holiday decorations: bells with "joy" and "peace" on them. Cal Poly Choirs? Dec. 6 ?Christmas Celebration? to Bring Holiday Cheer to Central Coast SAN LUIS OBISPO ? The holiday season is coming a little early to the Central Coast, by way of the Cal Poly Choirs? annual ?A Christmas Celebration,? set for 8 p.m. Saturday, Dec. 6, in Harman Hall of the Christopher Cohan Center. The University Singers, PolyPhonics and The Early Music Ensemble, conducted by Thomas Davies, will be joined by the Cal Poly Brass Ensemble, conducted by Christopher Woodruff. In addition the Cal Poly Barbershop Quartets and the a cappella ensemble Take It SLO will also perform. A variety of works from the 16th century to the present will be presented. The works include music by 16th-century composers Peter Philips and Michael Praetorius, 19th-century composer Mendelssohn, 20th-century composers Pavel Chesnokov, Randall Thompson, and Vaclav Nelhybel, and 21st-century composers Steven Stametz and Stephen Hatfield. Once again, PolyPhonics will be present a world premiere by Cal Poly composer Meredith Brammeier, titled ?A Christmas Lullaby.? This marks the seventh consecutive year that Brammeier has written a work for the Cal Poly Choirs? ?A Christmas Celebration.? The audience will have an opportunity to join in the holiday tradition of caroling. Tickets are $10 students, $16 and $19 seniors, $17 and $20 general and are on sale at the Performing Arts Ticket Office from 10 a.m. to 5 p.m. weekdays and 10 a.m. to 2 p.m. Saturdays. To order by phone, call SLO-ARTS (756-2787). Patrons who buy season tickets to four Music Department events through the Performing Arts Ticket office will receive a 10 percent discount; a 15 percent discount is given to those who buy tickets to five or more events. The holiday concert is sponsored by Cal Poly?s Music Department, College of Liberal Arts and Instructionally Related Activities program. For more information, call the Music Department at 756-2406.;